Parameter inference with estimated covariance matrices - Sellentin, Elena; Heavens, Alan (Monthly notices of the Royal Astronomical Society. Letters, 2016)
Abstract. When inferring parameters from a Gaussian-distributed data set by computing a likelihood, a covariance matrix is needed that describes the data error